Statistical Methods - Mills, F.C. (London Sir Isaac Pitman & Sons, 1955)
This book deals with a mode of inquiry- a method of investigating social and natural processes and of providing bases for decisions in research and administration.
Includes bibliographical references and index.
rua 14/11/16
Loans
Keywords: Statistics; Statistical methods